The association between maternal HIV and stillbirths in an era of universal art in pregnancy in the Western Cape, South Africa - Lubinda, Elizabeth (Department of Public Health and Family Medicine, 2025)
BACKGROUND: Annually, approximately 1.9 million stillbirths occur globally, with a rate of 13.9 per 1000 births. The devastating aftermath affects around 4.2 million mothers, and 75% of stillbirths are concentrated in South Asia and sub-Saharan Africa (SSA) particularly, with a rate of 32.2 per 1000 births in SSA. South Africa reported a stillbirth rate of 16.3 per 1000 births in 2019, despite global efforts to reduce stillbirth rates. SSA also faces the highest global HIV prevalence at 20%. South Africa, home to 8.4 million people living with HIV, grapples with a 30% prevalence among pregnant individuals. Antiretroviral therapy (ART) coverage for pregnant individuals reached 97% in 2019, especially in the Western Cape with an HIV prevalence of 17.9% among antenatal individuals. Quality antenatal care (ANC) is crucial, with research showing a lower stillbirth rate for those receiving higher quality ANC. The COVID-19 pandemic in 2020 introduced new challenges, potentially influencing stillbirth rates through factors like lockdowns and limited healthcare access. Pregnant individuals contracting SARS-CoV-2 faced an increased likelihood of stillbirth. In this context, our cohort study in the Western Cape, South Africa, utilized routine health data to investigate the contemporary relationship between pregnant individuals with HIV and stillbirths in the era of universal ART during pregnancy. The study explores associations with demographic and clinical variables, including the quality of ANC. METHODS Utilizing data from the Western Cape Pregnancy Exposure Registry (PER) between 2017 and 2021, this cohort study focused on pregnant women attending antenatal care (ANC) at the Gugulethu Midwife Obstetrics Unit (GMOU) and Worcester Midwife Obstetrics Unit (WMOU) in South Africa. Integrated information from the Provincial Health Data Centre (PHDC) was used to create a linked database for cohort generation. The cohort included women aged 18 or older, with known HIV status and a recorded pregnancy outcome after 20 weeks of gestation. The primary outcome was stillbirth, with maternal HIV status serving as the primary exposure. ANC quality, based on WHO guidelines, was assessed by considering variables such as ANC timing, the number of visits, and various healthcare parameters. ANC quality was categorized using both the old WHO guidelines (at least 4 visits) and the new WHO guidelines (at least 8 visits), with a good ANC quality score requiring 7 or more out of 11 quality ANC variables. Statistical analyses, including logistic regression, were conducted to explore associations between maternal HIV status, ANC quality, and stillbirth prevalence. The study also collected data on maternal characteristics to provide a comprehensive understanding of contributing factors. RESULTS The study included 15,123 participants: 4,773 women living with HIV (WLHIV) and 10,350 women without HIV. WLHIV had a median age of 28 years, while women without HIV had a median age of 31 years. The overall stillbirth rate was 15 per 1,000 births (95% CI: 13.1-16.9). Stillbirth rates were higher among WLHIV at 17 per 1,000 births (95% CI: 13.34-20.66) compared to women without HIV at 14 per 1,000 births (95% CI: 11.75-16.25). Maternal HIV- positive status (AOR = 1.15, 95% CI: 0.87-1.52, p = 0.34) did not show a statistically significant association with stillbirths. Women with prior diabetes exhibited a significant increase in stillbirth odds (AOR = 2.63, 95% CI: 1.06-6.52, p = 0.04). Women without HIV but with a history of diabetes had a stillbirth prevalence of 4.08%, compared to 3.80% for WLHIV. WLHIV with good-quality ANC had fewer stillbirths (4 visits: 5.06%, 8 visits: 2.53%) than women without HIV (4 visits: 11.56%, 8 visits: 5.06%). ART for ≥100 weeks among WLHIV showed a protective effect, with 47% lower stillbirth odds than ART <20 weeks (AOR = 0.53, p = 0.01) and 45% lower stillbirth odds than ART <20 weeks (AOR = 0.55, 95% CI: 0.33-0.91, p = 0.02). Despite higher stillbirth odds for WLHIV, no significant association was found between maternal HIV status and stillbirths after adjustment (AOR = 1.15, 95% CI: 0.87-1.52, p = 0.34). CONCLUSION: This study, utilizing routine program data, revealed no statistically significant difference in the prevalence of stillbirths between women living with and without HIV. Despite the lack of a statistically significant association between the quality of antenatal care (ANC) and stillbirths, the study underscores the importance of adhering to WHO recommendations and utilizing databases such as the Pregnancy Exposure Registry for evidence-based decision-making. Although the overall stillbirth rate slightly exceeded global targets, there was noticeable improvement following the universal rollout of antiretroviral therapy (ART). Notably, among women living with HIV (WLHIV), a longer duration of ART was linked to a significant reduction in the odds of stillbirth, highlighting the critical role of sustained access to ART. Despite its limitations, these findings contribute to global health objectives, particularly those aimed at eliminating preventable newborn deaths by 2030. ART emerges as a pivotal factor in decreasing stillbirth rates among women living with HIV.